Invasion and distribution range expansion of fall armyworm (Spodoptera frugiperda) in Azad Jammu & Kashmir, Pakistan (Zoo Botanica, 2025)
The Fall Armyworm (FAW) (Spodoptera frugiperda), a polyphagous pest, is rapidly expanding its distribution range and has invaded all areas of northern Pakistan. The current study was carried out to confirm the presence of FAW in the state of Azad Jammu & Kashmir (AJ&K). For this survey, three maize fields were selected from each district of administratively three divisions of AJ&K. This selection was based on surveying the FAW distribution and infestation and farmer reports on alarming maize yield losses due to large scale attack of FAW. Data on FAW infestation and invasion were collected from the extension wing, Department of Agriculture, AJ&K, and by fortnightly visits of selected localities. The overall results show the uniform distribution of FAW throughout the study area with very rapid dissemination to other areas and expansion of host range was also observed. This is the first study in Kashmir to report the occurrence of FAW in Kashmir. This study will be helpful for pest forecasting of FAW and planning management strategies to protect this important crop from the yield losses.
Keywords: Azad Jammu & Kashmir; fall armyworm; higher altitudes; maize; yield loss